Optimisation of Enzymatic Hydrolysis Condition of Soybean (Glycine Max (L.) Merr.) Tempeh Protein Hydrolysate Using Response Surface Methodology (RSM) - Saidatul Syida Wan Kamarudin, Wan; Abdullah, Noriham; Ismail, Normah; Yusuf Maskat, Mohamad (International Journal of Engineering and Technology, 2019)
The beneficial properties of overripe tempeh as a functional ingredient protein isolate are overlooked by most food manufacturers. The present study aims to optimise the enzymatic hydrolysis conditions to obtain tempeh protein hydrolysate (PH) that can be used as potential functional foods. The enzymatic hydrolysis (using Flavourzyme) conditions, namely, temperature (°C), enzyme to substrate concentration (%) and hydrolysis time (min) on both total flavonoid content (TFC) and glutamic acid content (GAC), as responses, were optimised using response surface methodology (RSM) by employing three factors, 3-level, and central composite rotatable design (CCRD). Enzyme inactivation was successfully performed by keeping the hydrolysate at 85°C in a water bath for 10 min. Based on the results, the optimum conditions for the hydrolysis of 6.0 g of soy protein isolate (SPI) from soybean tempeh were at temperature 55°C with 2.6% enzyme to substrate concentration heated for 128 min which resulted in 8.93 g QE/100 g DEW of TFC and 12.96 g/100 g DEW of GAC. The results also showed that TFC and GAC were significantly influenced by all the factors studied. Therefore, the results suggested that soybean by-product such as overripe tempeh can be converted into hydrolysate which is a good source of protein fortification of various food products as well as a potential functional food ingredient.